Response of 21 Hyaluronic Acid Fillers to Recombinant Human Hyaluronidase - Kristen E. Park, BA; Preeya Mehta, MD; Femida Kherani, MD; Wendy W. Lee, MD; Julie A. Woodward, MD; Jill A. Foster, MD; Sandy Zhang-Nunes, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. One benefit of hyaluronic acid fillers is the ability to dissolve them using hyaluronidase. With the increasing number of fillers entering the market, it is crucial to understand each of these fillers’ responsiveness to hyaluronidase. Methods:. Twenty-one hyaluronic acid fillers of 0.2 mL aliquots each were placed on slides. Twenty units of recombinant human hyaluronidase were injected into the aliquots every 30 minutes for a total of 120 units recombinant human hyaluronidase injected over 3 hours. With each injection, videos and photographs were taken from bird’s eye and lateral views to measure aliquot height. Stirring videos were graded by three oculoplastic surgeons, and these grades were used to categorize each filler’s responsiveness. Results:. Restylane Lyft, Restylane-L/Eyelight, and Resilient Hyaluronic Acid (RHA) 1/Redensity were the least resistant. The moderately resistant group comprised of Restylane Silk, Juvéderm Volbella, Revanesse Versa/Lips, and Belotero Balance on the less resistant side to Juvéderm Vollure, RHA 2, Restylane Contour, Juvéderm Ultra, Restylane Refyne, Belotero Intense, Restylane Kysse, RHA 3, Juvéderm Ultra Plus, and Restylane Defyne on the more resistant side. The most resistant were RHA 4, Juvéderm Voluma, Belotero Volume, and Juvéderm Volux. The most resistant fillers required 120 units of hyaluronidase per 0.2 mL filler to dissolve. Conclusions:. With the increasing popularity of fillers comes the increasing need to dissolve them for both ischemic and nonischemic complications. The majority of hyaluronic acid fillers available on the market are very resistant to hyaluronidase, which must be considered when determining the amount of hyaluronidase to dissolve a particular filler.